Menghadapi Quarter Life Crisis dalam Terang Perspektif Alkitab - Michael Salomo Hahuly (Sekolah Tinggi Teologi Baptis, Jakarta, 2021)
In this article we discuss all things related to one phase in life that is the quarter life crisis and how to deal with it from a biblical point of view. Quarter life crisis is a situation where everyone will definitely experience it. The explanation in this article covers the meaning, an indication of a person being present during the quarter life crisis, to which aspect of life is vulnerable when a person is present during this quarter life crisis, also how to deal with the quarter life crisis. Looking at it from the point of view of the peace that God has given to the nation of Israel, it is hoped that it can provide motivation for everyone who is in the phase of the quarter life crisis.AbstrakDalam artikel ini membahas tentang segala hal yang berhubungan dengan salah satu fase dalam kehidupan yaitu adalah quarter life crisis dan bagaimana cara menghadapinya berdasarkan sudut pandang Alkitab. Quarter life crisis adalah suatut keadaan dimana semua orang pasti akan mengalaminya. Penjelasan dalam artikel ini meliputi pengertian, indikasi seseorang sedang ada dalam masa quarter life crisis, hingga aspek kehidupan mana yang rawan ketika seseorang sedang ada dalam masa quarter life crisis ini, juga bagaimana cara menghadapi masa quarter life crisis. Dengan melihat dari sudut pandang bagaimana damai sejahtera yang Allah berikan kepada bangsa Israel, diharapkan dapat memberikan motivasi bagi setiap orang yang sedang berada dalam fase quarter life crisi